2015
DOI: 10.1111/hae.12667
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating between signs of intra‐articular joint bleeding and chronic arthropathy in haemophilia: a narrative review of the literature

Abstract: Despite the overlap in symptoms, differentiating between joint bleeds and flare-ups of HA based on clinical presentation still seems the most convenient and practical solution. Further research is necessary to identify specific symptoms that can be used to differentiate between the two conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 32 publications
2
44
0
4
Order By: Relevance
“…In this regard, appropriate assessment with imaging tools plays a role, especially for detection of early joint changes, since clinical assessment may underestimate abnormalities. Recent studies have highlighted the importance of imaging techniques in the assessment of early arthropathy, revealing abnormalities in joints that are almost asymptomatic on physical examination . If we consider synovitis as a parameter indicating active disease due to either inappropriate treatment or to problems related to low therapeutic adherence (eg, missing appointments and/or non‐compliant patients), this was found in a considerable number of HB patients treated OD: severe (grade 2) synovitis was observed in 18% of cases and moderate to severe (grade 1 + grade 2) synovitis in up to 57%.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, appropriate assessment with imaging tools plays a role, especially for detection of early joint changes, since clinical assessment may underestimate abnormalities. Recent studies have highlighted the importance of imaging techniques in the assessment of early arthropathy, revealing abnormalities in joints that are almost asymptomatic on physical examination . If we consider synovitis as a parameter indicating active disease due to either inappropriate treatment or to problems related to low therapeutic adherence (eg, missing appointments and/or non‐compliant patients), this was found in a considerable number of HB patients treated OD: severe (grade 2) synovitis was observed in 18% of cases and moderate to severe (grade 1 + grade 2) synovitis in up to 57%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Moreover, in patients with severe haemophilia, <15% experience pain in only 1 or 2 regions, while more than 35% report pain in at least 5 regions. 4 This unconditional association (acute pain relates to bleeding, and chronic pain is due to joint arthropathy) used in scientific literature and in clinical settings is remarkable. Traditionally, a differentiation is made between pain resulting from an acute bleed (haemarthrosis) and chronic pain originating from joint damage (arthropathy).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, a differentiation is made between pain resulting from an acute bleed (haemarthrosis) and chronic pain originating from joint damage (arthropathy). 1,4,7,8 A study comparing perceptions regarding the aetiology of pain in PwH with ultrasound evaluation confirmed that a diagnosis based on the sole perception of pain is unreliable in the majority of the cases: the aetiology of pain (bleeding versus joint inflammation or other regional pain syndrome) was correctly judged in only 30% of the cases, either by the physician or the patient! Firstly, the terms "acute" and "chronic" originally referred to a time frame and not to a specific underlying cause of pain.…”
Section: Introductionmentioning
confidence: 99%
“…Avoiding injection within four weeks of pending surgery recommended owing to HPA axis suppression ) Severe clotting abnormalities/bleeding disorders/ uncontrolled coagulopathy † Increased risk of bleeding complications with invasive procedure. Differentiating between haemarthorosis, haemophilic arthropathy and OA can be complex due to overlapping clinical signs (Roosendaal et al, 1999;Timmer et al, 2015). Specialist management suggested (Srivastava et al, 2013) Live vaccines.…”
Section: Pending Joint Surgerymentioning
confidence: 99%